2019
DOI: 10.5937/imk1903087p
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis and optimization of T and I cross sections of crane hook using by two physics-inspired algorithms

Abstract: Istraživačko-razvojni centar Alfatec d.o.o., Niš (Srbija) 2 Fakultet za mašinstvo i građevinarstvo u Kraljevu, Univerziteta u Kragujevcu, Kraljevo (Srbija) U ovom radu predstavljene su analiza i optimizacija geometrijskih parametara T i I poprečnih preseka dizalične kuke, posmatrane za najkritičnije mesto konstrukcije kuke. Smanjenje površine poprečnog preseka dizalične kuke postavljeno je kao glavni cilj u ovom istraživanju. Kao funkcije ograničenja posmatraju se naponi u karakterističnim tačkama najkritičnij… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…During maintenance and change, no change will occur in the mechanical properties of the box pro le material of the hatch cover stocking gantry crane, as it will not be welded. This, in turn, found that the strength values will be higher and safer than other studies [21][22][23].…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…During maintenance and change, no change will occur in the mechanical properties of the box pro le material of the hatch cover stocking gantry crane, as it will not be welded. This, in turn, found that the strength values will be higher and safer than other studies [21][22][23].…”
Section: Introductionmentioning
confidence: 64%
“…In other studies, the welded connection was made in the hook profile [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. For this reason, corrosion occurring in welding connections, etc.…”
Section: Strength Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, the welded connection was made in the hook pro le [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. For this reason, corrosion occurring in welding connections, etc.…”
Section: Strength Calculationsmentioning
confidence: 99%
“…Solving practical problems of design and optimization in engineering today is most often based on the application of different optimization algorithms. 14 There are many examples of successful application of optimization algorithms in solving problems of structural design of machine elements and constructions, such as those presented in Pavlović et al, 15 Abderazek et al, 16 Bižić et al, 17 Pavlović et al, 18 and Atanasovska and Momčilović. 19 Recent years, one of the most popular algorithms in solving the engineering and technical problems is Marine Predators Algorithm – MPA.…”
Section: Introductionmentioning
confidence: 99%